2005
DOI: 10.1242/jeb.01372
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activity of caudal neurosecretory neurons in seawater and freshwater-adapted Platichthys flesus, in vivo

Abstract: SUMMARY This study examined the electrical firing activity of neuroendocrine Dahlgren cells in the caudal neurosecretory system (CNSS) of the euryhaline flounder in vivo. Intracellular recordings revealed generally similar activity patterns and membrane properties to those previously reported in vitro. To investigate the potential role of the CNSS in osmoregulatory adaptation, extracellular, multiunit, recordings compared the activity patterns of Dahlgren cells in fully seawater- and freshwater-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…In our study, expression level of L-type Ca 2+ channel is lower in FW-adapted flounder CNSS than in SW-adapted flounder CNSS in both season. In consistent with our results, electrophysiological experiments have shown that bursting activity in Dahlgren cells is less robust in FW-adapted compared to SW-adapted fish (Ashworth et al, 2005;Brierley et al, 2003) and this is due, at least in part, to a reduction in Ca 2+ channel-dependent ADP and Ca-activated K + channels-dependent DAP (Brierley et al, 2003). In this study, we also examined L-type Ca 2+ channels or Ca-activated K + channels gene expression in fish transferred from SW to FW and reverse transfer.…”
Section: Effect Of Transfer Between Sw and Fw On L-type Ca 2+ Channelsupporting
confidence: 91%
“…In our study, expression level of L-type Ca 2+ channel is lower in FW-adapted flounder CNSS than in SW-adapted flounder CNSS in both season. In consistent with our results, electrophysiological experiments have shown that bursting activity in Dahlgren cells is less robust in FW-adapted compared to SW-adapted fish (Ashworth et al, 2005;Brierley et al, 2003) and this is due, at least in part, to a reduction in Ca 2+ channel-dependent ADP and Ca-activated K + channels-dependent DAP (Brierley et al, 2003). In this study, we also examined L-type Ca 2+ channels or Ca-activated K + channels gene expression in fish transferred from SW to FW and reverse transfer.…”
Section: Effect Of Transfer Between Sw and Fw On L-type Ca 2+ Channelsupporting
confidence: 91%
“…We then used CED Spike2 (version 5.17) software to assign spikes to a number of separate classes (OSNs). We have previously used this approach to reliably identify the activity of neuroendocrine cells in the spinal cord of fish in which characteristic patterned activity of neurons as seen in Spike2 analysis of extracellular multiunit recordings was mirrored by intracellular recordings of the activity of individual neurons (Brierley et al, 2003;Ashworth et al, 2005). Spike2 identifies neuronal events on the basis of amplitude and waveform (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the increase in CNSS CRF-related peptide mRNA levels in response to hyperammonemia and hypoxia are unlikely to result from the stimulation of osmoreceptorsensitive regulatory pathways. Instead, since electrical stimulation of branchial nerve branches can affect Dahlgren cell activity (Ashworth et al 2005), we raise the possibility that the afferent fibers from the gill chemoreceptors involved in mediating hypoxic reflexes also synapse onto descending pathways that reach the CNSS. In contrast, if ammonia neurotoxicity in fish results from a local synaptic excess of glutamate as proposed by Walsh et al (2007), then the stimulatory effects of hyperammonemia on the CRF-and UI-expressing cells of the CNSS are more likely to be of local rather than extrinsic origin.…”
Section: Contrasting Effects Of Stressors On the Expression Of Crf Anmentioning
confidence: 99%
“…Indeed, the results from electrophysiological and pharmacological studies suggest that the Dahlgren cells are subject to a complex balance of excitatory and inhibitory input of both extrinsic and intrinsic origin (see for review). To date, however, only one type of stressor, osmotic disturbances, has been shown to activate descending pathways that modulate Dahlgren cell activity (Ashworth et al 2005). While hyperammonemia and hypoxia may elicit small ionic disturbances (Thomas et al 1986, Knoph & Thorud 1996, the changes in CNSS CRF and UI expression in response to these stressors differ markedly from those elicited by seawater transfer .…”
Section: Contrasting Effects Of Stressors On the Expression Of Crf Anmentioning
confidence: 99%